Cross-cultural adaptation and validation of the rapid assessment of physical activity questionnaire (RAPA) in Hungarian elderly over 50 years - Erika Viktória Miszory; Alexandra Makai; Annamária Pakai; Melinda Járomi (BMC, 2022)
Abstract Background Reliable and valid instruments are needed to estimate physical activity levels. The aim was to culturally adapt the "Rapid Assessment of Physical Activity" (RAPA) into Hungarian and to investigate the validity and reliability of this adapted version in the elderly over 50 years. Methods In our cross-sectional study 222 subjects were recruited in Hungary between December 2020 and January 2021(age 61.1 ± 7.9 years, 28% male). Criterion validity of RAPA and International Physical Activity Questionnaire (IPAQ)-Hungarian long version was tested by Spearman's rank correlation. The examination of repeatability was based on a group of 32 people, and on the one-week test-retest reliability approach, and in addition to this during the statistical analysis intra-class correlation coefficient was calculated. To examine the sensitivity and specificity of the RAPA, negative and positive physical activity values were calculated from the results of the long version of the IPAQ and the RAPA. We tested 4 hypotheses (3 validity, 1 reliability). We considered acceptable validity and reliability if > 75% of hypotheses were confirmed. Results: All of the hypotheses (100%) were confirmed. Based on results of the validity testing of the newly adapted questionnaire was showed a moderate correlation between the examined measurement tools (R = 0.542, p < 0.001). The test-retest results of the questionnaire (N = 32, R = 0.988, p < 0.001) showed strong association. Conclusion RAPA showed fair to moderate validity and strong test-retest reliability similar to other studies. Based on our study's results the RAPA is a valid and reliable questionnaire to measure the elderly Hungarian population's physical activity.